2016
DOI: 10.1039/c6ra15382h
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of α-zirconium phosphate by polyphosphazene and its effect on the flame retardance of an intumescent flame retardant polypropylene system

Abstract: α-ZrP was combined with polyphosphazene and formed a core–shell structure, which has a significant synergistic flame retardant performance in polypropylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The higher the degree of graphitization, the lower the I D /I G ratio and the denser the char layer. 38 In Figure 12, shows that the surface of the char residual of TPU-0 is severely damaged and porous with little residual. Compared with neat TPU, the composites' char residue material was expanded and the number of pores on the surface was reduced, which was attributed mainly to the expanded flame retardation of IFR.…”
Section: Thermal Conductivity Of Tpu Compositesmentioning
confidence: 99%
“…The higher the degree of graphitization, the lower the I D /I G ratio and the denser the char layer. 38 In Figure 12, shows that the surface of the char residual of TPU-0 is severely damaged and porous with little residual. Compared with neat TPU, the composites' char residue material was expanded and the number of pores on the surface was reduced, which was attributed mainly to the expanded flame retardation of IFR.…”
Section: Thermal Conductivity Of Tpu Compositesmentioning
confidence: 99%
“…Second, a small amount of phosphorus monoxide (PO•) produced by the combustion of OZrP can quench active radicals produced by the burning of the gas phase, while the exfoliated OZrP layers can efficiently promote the formation of compact F 2: Flame retardant mechanisms of partial two-dimensional materials. (a) e free radicals of PP chain scission are inhibited, and then a coherent, thermally stable, and tough swollen char is formed under the catalysis of solid acid sites on the surface of a-zrp core [59]. (b) LDHs catalyze the formation of a thick char layer on the surface of EP [60].…”
Section: Gas Phase Free Radical Inhibitionmentioning
confidence: 99%
“…erefore, solid acid-type α-ZrP can play an effective role as a crosslinking catalyst through the catalysis of carbonization of the polymer itself during thermal decomposition [93]. However, two main subjects have to be addressed before their further applications as flame retardants: the inherent agglomeration of nano-sized α-ZrP and their incompatibility with polymers [59,63,67,.…”
Section: Nitrogen-containing Compoundsmentioning
confidence: 99%
“…The EDS analysis suggested that the AM-ZrP in the PPA/AM-ZrP composite acted as catalyst for the char layer production, and promoted the formation of compact char layer, resulting in the good ame retardancy of the composite. 33,34…”
Section: Effects Of Am-zrp On the Ame Retardancymentioning
confidence: 99%